Shape-selective recognition of DNA abasic sites by metallohelices: inhibition of human AP endonuclease 1 - Malina, Jaroslav; Scott, Peter; Brabec, Viktor (Nucleic acids research, 2015)
Loss of a base in DNA leading to creation of an abasic (AP) site leaving a deoxyribose residue in the strand, is a frequent lesion that may occur spontaneously or under the action of various physical and chemical agents. Progress in the understanding of the chemistry and enzymology of abasic DNA largely relies upon the study of AP sites in synthetic duplexes. We report here on interactions of diastereomerically pure metallo-helical 'flexicate' complexes, bimetallic triple-stranded ferro-helicates [Fe2(NN-NN)3](4+) incorporating the common NN-NN bis(bidentate) helicand, with short DNA duplexes containing AP sites in different sequence contexts. The results show that the flexicates bind to AP sites in DNA duplexes in a shape-selective manner. They preferentially bind to AP sites flanked by purines on both sides and their binding is enhanced when a pyrimidine is placed in opposite orientation to the lesion. Notably, the Λ-enantiomer binds to all tested AP sites with higher affinity than the Δ-enantiomer. In addition, the binding of the flexicates to AP sites inhibits the activity of human AP endonuclease 1, which is as a valid anticancer drug target. Hence, this finding indicates the potential of utilizing well-defined metallo-helical complexes for cancer chemotherapy.
Keywords: DNA Damage; Ferrous Compounds; DNA footprinting; vazebná místa; 2-aminopurin; DNA-(Apurinic or Apyrimidinic Site) Lyase; Enzyme Inhibitors; DNA; denaturace nukleových kyselin; Antineoplastic Agents; protinádorové látky; 2-Aminopurine; DNA Footprinting; poškození DNA; kalorimetrie; inhibitory enzymů; DNA-lyasa (apurinová nebo apyrimidinová); amilorid; Calorimetry; železnaté sloučeniny; Amiloride; Nucleic Acid Denaturation; Binding Sites